2014
DOI: 10.1038/cddis.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of osmotin against ethanol-induced apoptotic neurodegeneration in the developing rat brain

Abstract: Fetal alcohol syndrome is a neurological and developmental disorder caused by exposure of developing brain to ethanol. Administration of osmotin to rat pups reduced ethanol-induced apoptosis in cortical and hippocampal neurons. Osmotin, a plant protein, mitigated the ethanol-induced increases in cytochrome c, cleaved caspase-3, and PARP-1. Osmotin and ethanol reduced ethanol neurotoxicity both in vivo and in vitro by reducing the protein levels of cleaved caspase-3, intracellular [Ca2+]cyt, and mitochondrial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…Early indications suggest that in embryonic neurons, NF‐κB translocation stimulated by tumour NF alpha promotes neuron survival, possibly by inducing the expression of anti‐apoptotic proteins such as Bcl‐2 and Bcl‐x . The important contribution of Bcl‐2 to apoptotic processes in hippocampal neurons is now especially well documented . Moreover, several studies have linked the reduction of Bcl‐2 expression to the neuronal damage in the CNS after exposure to anaesthetics .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early indications suggest that in embryonic neurons, NF‐κB translocation stimulated by tumour NF alpha promotes neuron survival, possibly by inducing the expression of anti‐apoptotic proteins such as Bcl‐2 and Bcl‐x . The important contribution of Bcl‐2 to apoptotic processes in hippocampal neurons is now especially well documented . Moreover, several studies have linked the reduction of Bcl‐2 expression to the neuronal damage in the CNS after exposure to anaesthetics .…”
Section: Discussionmentioning
confidence: 99%
“…40 The important contribution of Bcl-2 to apoptotic processes in hippocampal neurons is now especially well documented. 41 Moreover, several studies have linked the reduction of Bcl-2 expression to the neuronal damage in the CNS after exposure to anaesthetics. [42][43][44] Apoptosis is strictly controlled by multiple gene families, including not only the Bcl-2 but also the caspase families.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol-induced neurotoxicity models have previously been used to study NDDs (Naseer et al, 2014; Saito et al, 2016). In vivo and in vitro studies have shown that chronic ethanol exposure elevates GluN1 and GluN2B gene expression and their polypeptide levels.…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%
“…A recent study in animals showed that plant osmotin can activate a pathway involved in disease resistance by binding to the adiponectin receptors. Through the upregulation of the antiapoptotic Bcl-2 protein, plant osmotin reduces ethanol neurotoxicity and reverses synaptic dysfunction and neuronal apoptosis (Naseer et al 2014 andShah et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Osmotin reduces ethanol neurotoxicity via the upregulation of the antiapoptotic Bcl-2 protein, and reverses synaptic dysfunction and neuronal apoptosis. The Bcl-2 protein appears to block a distal step in a common pathway for apoptosis and programmed cell death (Naseer et al 2014 andShah et al 2014). …”
Section: Introductionmentioning
confidence: 99%